Above‐ and belowground biotic interactions facilitate relocation of plants into cooler environments. (18th March 2014) - Spasojevic, Marko J.; Harrison, Susan; Day, Howard W.; Southard, Randal J.; Cleland, Elsa
Abstract One important but largely unanswered question about floristic responses to climate change is how interactions such as competition, facilitation and plant–soil feedbacks will influence the ability of species to track shifting climates. In a rugged and moisture‐limited region that has recently warmed by 2° (Siskiyou Mountains, OR, USA), we planted three species into cooler aspects and elevations than those they currently inhabit, with and without removal of neighbouring plants, and tracked them over 2 years. Two species had higher success in cooler topographic locations, and this success was enhanced by neighbouring plants, which appeared to modulate minimum growing season temperatures. One species' success was also facilitated by the higher soil organic matter found in cooler sites. These results are a novel experimental demonstration of two important factors that may buffer climate change impacts on plants: rugged topography and plant–plant facilitation.